Thrombomodulin: A New Marker for Placental Abruption - Magriples, Urania; Chan, Daniel W.; Bruzek, Debra; Copel, Joshua A.; Hsu, Chaur-Dong (Thrombosis and Haemostasis, 1999)
Thrombomodulin (TM), a marker of endothelial cell damage, has been localized to the placental syncytiotrophoblast. A prospective cohort study of twenty-five pregnant women who were admitted with a clinical diagnosis of placental abruption was undertaken. Abruption was confirmed after delivery in eight cases (Group 1). Group 2 consisted of seventeen patients with no clinical or pathologic evidence of placental abruption after delivery. TM was significantly elevated in Group 1 (71.59 ± 5.35 vs. 48.29 ± 3.53 ng/ml, p = 0.001). The sensitivity and specificity of TM ≥60 ng/ml as a marker for abruption was 87.5 and 76.5%, respectively. In comparison, the sensitivity of an abnormal coagulation profile, maternal Kleihauer-Betke and ultrasound in patients with abruption was 0, 16.7 and 28.6%, respectively. TM is a highly sensitive and specific marker for acute placental abruption.